Progress Toward the 90-90-90 HIV Targets in Zimbabwe and Identifying Those Left Behind. (1st November 2021) - Hakim, Avi J.; Tippett Barr, Beth A.; Kinchen, Steven; Musuka, Godfrey; Manjengwa, Julius; Munyati, Shungu; Gwanzura, Lovemore; Mugurungi, Owen; Ncube, Getrude; Saito, Suzue; Parekh, Bharat S.; Patel, Hetal; et al.
Abstract : Objective: We present findings from the nationally representative Zimbabwe Population–based HIV Impact Assessment that characterize Zimbabwe's progress toward the Joint United Nations Programme on HIV/AIDS 90-90-90 targets. Design: We conducted a cross-sectional household survey. Methods: Consenting adults and children in the household were eligible to participate in Zimbabwe Population–based HIV Impact Assessment (October 2015–August 2016). Participants completed face-to-face interviews and provided blood for HIV, CD4, viral load, and syphilis testing. Viral load suppression (VLS) was defined as HIV RNA <1000 copies/mL. HIV-positive specimens were tested for the presence of selected antiretroviral drugs. Data were weighted. Analysis was restricted to HIV-positive adults aged 15–64 years. Results: We enrolled 11, 098 men and 14, 033 women aged 15–64 years. HIV prevalence was 14.1%. Of those living with HIV, 76.8% (95% confidence interval [CI]: 74.9 to 78.7) were aware of their HIV status or had detectable antiretroviral levels. Of these, 88.4% (95% CI: 87.1 to 89.7) were receiving antiretroviral therapy (ART), and of these people, 85.3% (95% CI: 83.4 to 87.1) had VLS. Male sex age 15–34 years and having 1 or more sexual partners were associated with being unaware of one's HIV-positive status. Age <50 years and not taking cotrimoxazole were associated with being less likely to be being both aware and taking ART. Male sex, age <50 years, and taking cotrimoxazole were associated with being on ART but not having VLS. Conclusions: Zimbabwe has made great strides toward epidemic control. Focusing resources on case finding, particularly among men, people aged <35 years, and sexually active individuals can help Zimbabwe attain 90-90-90 targets.